INTEGRASI MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN PENDEKATAN RME UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Cahya Nilam Maharani; Eko Andy Purnomo; Iswahyudi Joko Suprayitno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students are required to process mathematical problem-solving skills to meet the demands of 21St- century education. Various instructional models have been developed to enhance these skills, including the integration of Discovery Learning (DL) and Realistic Mathematics Education (RME). This study employed a Systematic Literature Review (SLR) approach by examining sixteen Sinta – indexed articles (levels 2-5) relevant to the topic of mathematical problem – solving abilities. The findings reveal that most studies applied Polya’s problem – solving strategy and emphasized the importance of contextual learning and systematic thinking processes. The integration of DL and RME has been Shown to be effective in optimizing problem – solving through independent concept discovery connected to real-life context. In addition to improving conceptual understanding, this combination also fosters students’ independence, creativity, and reflective thinking skills. Therefore, integrating DL and RME can serve as an innovative instructional alternative that support the strengthening of Higher – Order Thinking Skills (HOTS) in alignment with the goals of the Merdeka Curriculum